2018
DOI: 10.4187/respcare.06058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maximum Dynamic Inspiratory Pressure

Abstract: Eight maneuvers were necessary to reach maximum and reliable values of the S-Index preceding inspiratory muscle warm-up or sham. Moreover, inspiratory muscle warm-up preceding S-Index assessment improved inspiratory muscle performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
1
21
1
5
Order By: Relevance
“…24,25 Some factors, including anesthesia and surgery, have been associated with a decrease in this parameter. 26 IMT has been reported to serve as an option for minimizing these losses, 8,27,28,29 and our study corroborated this finding. Patients who received IMT had similar MIP values in the preoperative and postoperative periods of cardiac surgery.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…24,25 Some factors, including anesthesia and surgery, have been associated with a decrease in this parameter. 26 IMT has been reported to serve as an option for minimizing these losses, 8,27,28,29 and our study corroborated this finding. Patients who received IMT had similar MIP values in the preoperative and postoperative periods of cardiac surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Patients who received IMT had similar MIP values in the preoperative and postoperative periods of cardiac surgery. 8,28,29 Therefore, IMT may be an important strategy for minimizing respiratory muscle weakness due to cardiac surgery. 28 Hulzelbos et al 30 reported that maintaining or increasing respiratory muscle strength is important to reduce the effects of pulmonary complications and has even decreased the length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva et al 27 evaluated the S-Index of 81 healthy adults, obtaining a mean of 102 cmH 2 O. These values are higher than the mean obtained in our study with healthy children and adolescents, with a mean value of 87.10 cmH 2 O.…”
Section: Discussioncontrasting
confidence: 77%